The Effect of Using Authentic Materials to Enhance Students’ Reading Comprehension Achievement - Nida Nafisah; Anik Nunuk Mulyani (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2024)
This research explored the influence of utilizing authentic texts as reading materials on the reading performance of high school students and their perceptions of these materials. It addressed the gap in existing studies that predominantly relied on qualitative methods, which lacked quantitative data on the impact of authentic texts on students' reading achievement. The study employed a pre-experimental one-group pretest-posttest design, involving 21 second-year students from a senior high school in Situbondo, East Java, during the 2021/2022 academic period. The instruments used included pre-tests and post-tests to assess reading achievement and questionnaires to capture students' perceptions of the materials. The data were analyzed using a paired sample t-test to determine the significance of the changes in reading scores and descriptive analysis for the questionnaire results. The findings revealed a significant improvement in reading scores, with an average increase of 19.25 points, indicating the effectiveness of authentic texts in enhancing reading comprehension and vocabulary retention. The questionnaire results also showed that the majority of students found the materials engaging and beneficial for learning. This research underscored the importance of integrating real-life texts into the curriculum to bridge the gap between classroom learning and practical language use. The study provided quantitative evidence supporting the benefits of authentic materials in language education, suggesting that their use could significantly improve reading achievement and learner motivation. These insights could inform educators and curriculum developers in enhancing language instruction strategies.